AKTIVITAS HARIAN DAN DETEKSI STRES PADA SAPI PERANAKAN ONGOLE (PO) DAILY ACTIVITIES AND DETECTION OF STREE ON PO CATLE BY MEASUREMENT OF CORTISOL HORMONE LEVELS - Jauhari Efendy (Maduranch : Jurnal Ilmu Peternakan, 2018)
The study aims to observe behavior and stress levels to PO cattles in group housing of "Balitbangtan Model". Materials research using 72 PO cattles are placed in group housing which is divided into 12 blocks each measuring 3 x 6 meters. Techniques of data collection is done through behaviour observation outside the housing for 24 hours using intermittent method. Blood sampling conducted in the morning starting at 08:30 up to 9:30 am for six days using venoject tube through the jugular vein in the neck of the cattle. Activities stand the daily behaviour of the dominant bulls performed (60.21%) and cows (51.40%) during the day on all treatments. Activities carried out by livestock lying on all treatments in time almost equally well at day or night. Sleep activity is only done at night with long time percentage of 44.15% in bulls and 29.27% in cows. The average levels of the PO cattle cortisol in each treatment was not significantly different, respectively 21.39 ng / mL and 36.48 ng / mL. Based on observations per individual, there are 10 heads that had cortisol levels above normal; of that number 6 tails are in the extreme category (above 80 ng / mL) so that it can be categorized that animals are stressed high enough